2020
DOI: 10.3389/fimmu.2020.571083
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Platelet-Generated Amyloid Beta Peptides in Certain Amyloidosis Health Complications

Abstract: As do many other immunity-related blood cells, platelets release antimicrobial peptides that kill bacteria, fungi, and even certain viruses. Here we review the literature suggesting that there is a similarity between the antimicrobials released by other blood cells and the amyloid-related Aβ peptide released by platelets. Analyzing the literature, we also propose that platelet-generated Aβ amyloidosis may be more common than currently recognized. This systemic Aβ from a platelet source may participate in vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 217 publications
(276 reference statements)
0
16
0
Order By: Relevance
“…However, it was recently shown that Aβ oligomers inhibit the growth of various human cancer cells, including breast carcinoma cells [ 31 ]. Thus, there is the possibility that platelet‐generated Aβ is produced in response to cancer development and released in tumors, as we suggested previously [ 24 ].…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…However, it was recently shown that Aβ oligomers inhibit the growth of various human cancer cells, including breast carcinoma cells [ 31 ]. Thus, there is the possibility that platelet‐generated Aβ is produced in response to cancer development and released in tumors, as we suggested previously [ 24 ].…”
mentioning
confidence: 66%
“…While it is known that APP is present in IBC, we found no published evidence on whether APP is cleaved to form Aβ peptides and aggregated Aβ amyloid in breast cancer. However, besides carcinoma cells themselves, another blood‐related systemic source of Aβ peptide production may lead to its accumulation in tumors [ 23 , 24 ]. Recently, we found that platelets trigger a massive release of Aβ after thrombosis and that this release is concentrated near blood vessels [ 25 , 26 ].…”
mentioning
confidence: 99%
“…Indeed, outside of CNS, platelets are known as the main source of Aβ (Veitinger et al, 2014 ; Inyushin et al, 2020 ). Thus, the cellular mechanisms of AD can be effectively studied using platelet sample preparations, due to dramatically increased levels of the Aβ precursor protein (APP) in them in comparison to all peripheral tissues, and all three isoforms of APP (130, 110, and 106 kDa) being detectable within platelets.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…The family of serum amyloid A proteins encoding genes have been well conserved throughout vertebrate evolution [102,103]. Platelet generated amyloid beta (Aβ) amyloidosis may be more common than currently recognized [113]. In cancer cells in the breast and prostate, the process of amyloidosis induces cells to enter a dormant or resting stage [114] and cell lines studies have indicated that amyloid β oligomers inhibit growth of human cancer cells [115].…”
Section: Amyloidosismentioning
confidence: 99%